Brassinosteroids tailor stomatal production to different environments - Gudesblat, Gustavo Eduardo (2012)
Two recent reports show that brassinosteroids control stomata production by regulating the GSK3-like kinase BIN2-mediated phosphorylation of two different stomatal signalling components resulting in opposite stomatal phenotypes. We discuss how these two mechanisms might differentially control stomatal generation under diverse growth conditions. © 2012 Elsevier Ltd.